2017
DOI: 10.3389/fnagi.2017.00290
|View full text |Cite
|
Sign up to set email alerts
|

Combining SPECT and Quantitative EEG Analysis for the Automated Differential Diagnosis of Disorders with Amnestic Symptoms

Abstract: Single photon emission computed tomography (SPECT) and Electroencephalography (EEG) have become established tools in routine diagnostics of dementia. We aimed to increase the diagnostic power by combining quantitative markers from SPECT and EEG for differential diagnosis of disorders with amnestic symptoms. We hypothesize that the combination of SPECT with measures of interaction (connectivity) in the EEG yields higher diagnostic accuracy than the single modalities. We examined 39 patients with Alzheimer's dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 92 publications
(110 reference statements)
0
11
0
1
Order By: Relevance
“…We identified twenty-four studies which used neurophysiological imaging methods, only three of which investigated non-AD dementias including PD and FTD (Garn et al 2017;Ruffini et al 2019;Dottori et al 2017). The majority of the studies (n=21) used quantitative EEG while the remaining used either MEG (Furutani et al 2020), event-related potential EEG (Chapman et al 2011) or combined EEG with SPECT (Höller et al 2017). Although half (n=12) of these studies were published since 2018, this cohort of publications also included some of the earliest papers identified in this review starting in 2005 (Dauwels et al 2010;Cichocki et al 2005).…”
Section: Neurophysiological Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified twenty-four studies which used neurophysiological imaging methods, only three of which investigated non-AD dementias including PD and FTD (Garn et al 2017;Ruffini et al 2019;Dottori et al 2017). The majority of the studies (n=21) used quantitative EEG while the remaining used either MEG (Furutani et al 2020), event-related potential EEG (Chapman et al 2011) or combined EEG with SPECT (Höller et al 2017). Although half (n=12) of these studies were published since 2018, this cohort of publications also included some of the earliest papers identified in this review starting in 2005 (Dauwels et al 2010;Cichocki et al 2005).…”
Section: Neurophysiological Imagingmentioning
confidence: 99%
“…APOE4 status and cognitive scores) to train a classifier, then selected neuroimaging features for classification, showing better performance when neuroimaging data (grey matter density, amyloid burden, APOE4 status; r = -0.68) were used to predict individualised rate of cognitive decline in MCI, compared to cognitive predictors (depression, memory and executive function scores; r = -0.4) (Giorgio et al 2020). Similarly, three studies showed that SPECT is able to classify MCI and AD, but its predictive value for MCI conversion is improved when combined with other imaging modalities or cognitive assessments (Borroni et al 2006;Holler et al 2017;Habert et al 2011).…”
Section: Pet/spect Imagingmentioning
confidence: 99%
“…In 2017, Höller et al (22) combined quantitative markers from SPECT and electroencephalography (EGG) for differential diagnosis of disorders with amnestic symptoms. The classification was again accomplished by SVM algorithm.…”
Section: Alzheimer's Disease (Ad) Diagnosismentioning
confidence: 99%
“…Die Schwere einer Enzephalopathie lässt sich mittels EEG gut bestimmen. Die Kombination nuklearmedizinischer Methoden (SPECT) und quantitativem EEG verbessert die Differenzierung zwischen neurodegenerativ und depressiv bedingten Gedächtnisbeschwerden [28].…”
Section: Enzephalopathienunclassified